Simultaneous cell growth and ethanol production from cellulose by an engineered yeast consortium displaying a functional mini-cellulosome - Goyal, Garima (BioMed Central, 2011)
BACKGROUND: The recalcitrant nature of cellulosic materials and the high cost of enzymes required for efficient hydrolysis are the major impeding steps to their practical usage for ethanol production. Ideally, a recombinant microorganism, possessing the capability to utilize cellulose for simultaneous growth and ethanol production, is of great interest. We have reported recently the use of a yeast consortium for the functional presentation of a mini-cellulosome structure onto the yeast surface by exploiting the specific interaction of different cohesin-dockerin pairs. In this study, we engineered a yeast consortium capable of displaying a functional mini-cellulosome for the simultaneous growth and ethanol production on phosphoric acid swollen cellulose (PASC). RESULTS: A yeast consortium composed of four different populations was engineered to display a functional mini-cellulosome containing an endoglucanase, an exoglucanase and a β-glucosidase. The resulting consortium was demonstrated to utilize PASC for growth and ethanol production. The final ethanol production of 1.25 g/L corresponded to 87% of the theoretical value and was 3-fold higher than a similar yeast consortium secreting only the three cellulases. Quantitative PCR was used to enumerate the dynamics of each individual yeast population for the two consortia. Results indicated that the slight difference in cell growth cannot explain the 3-fold increase in PASC hydrolysis and ethanol production. Instead, the substantial increase in ethanol production is consistent with the reported synergistic effect on cellulose hydrolysis using the displayed mini-cellulosome. CONCLUSIONS: This report represents a significant step towards the goal of cellulosic ethanol production. This engineered yeast consortium displaying a functional mini-cellulosome demonstrated not only the ability to grow on the released sugars from PASC but also a 3-fold higher ethanol production than a similar yeast consortium secreting only the three cellulases. The use of more complex cellulosomal structures may further improve the overall efficiency for ethanol production.